PENGARUH SENAM HAMIL TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER 3 DI TPMB BDN. UUM SUMIATI, SST. M.SI - Nurhidayah, Wariah; Musmundiroh, Musmundiroh (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anxiety during pregnancy is a feeling of discomfort or vague worry accompanied by an autonomic response, the impact is so great for the mother and fetus that intervention is necessary, namely pregnancy exercise. The aim of this study was to determine the effect of pregnancy exercise on anxiety levels in pregnant women in the third trimester at TPMB Bdn. Uum Sumiati, SST. M.Si.The research method used was a quasi experiment with a one group pretest-posttest design. The research used primary data with a sample of 39 third trimester pregnant women who took part in pregnancy exercise. The instrument used to measure anxiety levels is The Perinatal Anxiety Screening Scale (PASS). The sampling technique uses purposive sampling technique. Data analysis used the Wilcoxon test.The results of the Wilcoxon test data analysis showed a p value of 0.007 (<0.05), indicating that pregnancy exercise can reduce anxiety in pregnant women in the third trimester at TPMB Bdn. Uum Sumiati. SST. M.Si.The conclusion in this study is that there is an influence of pregnancy exercise on the level of anxiety in pregnant women in the third trimester at TPMB Bdn. Uum Sumiati SST. M.Si. Keywords: Pregnant Women, Anxiety, Pregnancy exercise